The Role of Trust and Knowledge Sharing in Encouraging Innovative Work Behavior: An Empirical Study of SMEs in Tarakan City - Nurul Hidayat; Dean Nelson Mojolou; Fearozh Madli; Suddin Lada; Ang Hong Loong (Advances in Human Resource Management Research, 2026)
Purpose: This study aims to examine the role of trust (horizontal and vertical) and knowledge sharing (knowledge donation and knowledge collection) in enhancing innovative work behavior (idea generation and idea realization) among SMEs in Tarakan City. The main issue addressed is the low level of innovation capacity influenced by relational factors and knowledge management practices. Research Method: This research employs a quantitative explanatory design. Data were collected through Likert-scale questionnaires from 150 SME actors using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (SEM-PLS) software. Results and Discussion: The results indicate that both horizontal and vertical trust positively influence knowledge donating and knowledge collecting. Knowledge donating significantly affects idea generation and idea realization, while idea generation strongly influences idea realization. However, knowledge collecting does not significantly affect innovative work behavior. These findings suggest that innovation is primarily driven by active knowledge contribution rather than passive knowledge acquisition. Implications: This study highlights the importance of fostering a trust-based organizational culture and promoting knowledge-donating practices to enhance SME innovation, while also contributing to the development of knowledge management theory in the SME context.